How can we support best practice? A situational assessment of injury prevention practice in public health - Sarah A. Richmond (BMC Public Health, 2020)
Abstract Background To effectively impact the significant population burden of injury, we completed a situational assessment of injury prevention practice within a provincial public health system to identify system-wide priorities for capacity-building to advance injury prevention in public health. Methods A descriptive qualitative study was used to collect data on the current practice, challenges and needs of support for injury prevention. Data was collected through semi-structured interviews (n = 20) and focus groups (n = 19). Participants included a cross-section of injury prevention practitioners and leadership from public health units reflecting different population sizes and geographic characteristics, in addition to public health researchers and experts from academia, public health and not-for-profit organizations. Thematic analysis was used to code all of the data by one reviewer, followed by a second independent reviewer who coded a random selection of interview notes. Major codes and sub codes were identified and final themes were decided through iterations of coding comparisons and categorization. Once data were analysed, we confirmed the findings with the field, in addition to participating in a prioritization exercise to surface the top three needs for support. Results Major themes that were identified from the data included: current public health practice challenges; capacity and resource constraints, and; injury as a low priority area. Overall, injury prevention is a broad, complex topic that competes with other areas of public health. Best practices are challenged by system-wide factors related to resources, direction, coordination, collaboration, and emerging injury public health issues. Injury is a reportedly under prioritized and under resourced public health area of practice. Practitioners believe that increasing access to data and evidence, and improving collaboration and networking is required to promote best practice. Conclusions The results of this study suggest that there are several system level needs to support best practice in public health injury prevention in Ontario including reducing research to practice gaps and supporting opportunities for collaboration. Our research contributes to the literature of the complexity of public health practice, and presents several mechanisms of support to increase capacity at a system level to improve injury prevention practice, and eventually lessen the population burden of injury.